2016
DOI: 10.18632/oncotarget.11151
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of uracil DNA glycosylase sensitizes cancer cells to 5-fluorodeoxyuridine through replication fork collapse-induced DNA damage

Abstract: 5-fluorodeoxyuridine (5-FdU, floxuridine) is active against multiple cancers through the inhibition of thymidylate synthase, which consequently introduces uracil and 5-FU incorporation into the genome. Uracil DNA glycosylase (UDG) is one of the main enzymes responsible for the removal of uracil and 5-FU. However, how exactly UDG mediates cellular sensitivity to 5-FdU, and if so whether it is through its ability to remove uracil and 5-FU have not been well characterized. In this study, we report that UDG deplet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 51 publications
2
31
0
Order By: Relevance
“…However, previous studies have recently expanded the mechanism of action and cytotoxicity of 5-FU to include its incorporation into RNA products (Silverstein et al, 2011). Subsequent studies have similarly shown that 5-FdU is phosphorylated to serve as a direct substrate for DNA misincorporation, thereby exacerbating its cytotoxic effects (Yan et al, 2016). Our data support this latter role of 5-FdU in mediating carcinoma cytotoxicity, as we demonstrate that the low-fidelity telomerase reverse-transcriptase readily misincorporates non-native nucleotide analogs, including 5-FdU, into its telomere DNA products.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, previous studies have recently expanded the mechanism of action and cytotoxicity of 5-FU to include its incorporation into RNA products (Silverstein et al, 2011). Subsequent studies have similarly shown that 5-FdU is phosphorylated to serve as a direct substrate for DNA misincorporation, thereby exacerbating its cytotoxic effects (Yan et al, 2016). Our data support this latter role of 5-FdU in mediating carcinoma cytotoxicity, as we demonstrate that the low-fidelity telomerase reverse-transcriptase readily misincorporates non-native nucleotide analogs, including 5-FdU, into its telomere DNA products.…”
Section: Discussionmentioning
confidence: 99%
“…In these cases, the remaining cytotoxic effects are likely due to inhibition of thymidylate synthase and/or misincorporation of 5-FdU or deoxyuridine (a by-product of thymidylate synthase inhibition) into genomic DNA. Indeed, both uracil and 5-FU moieties are detected in genomic DNA after treating cells with 5-FdU (Yan et al, 2016). These dual effects are likely recapitulated at the telomere upon treatment of 5-FdU.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Supplementary Figure S1B-C, UGI expression and drug (5FdUR or RTX) treatment led to significantly increased uracil content in genomic DNA. It is important to note that either UGI expression or treatments with drugs targeting de novo thymidylate biosynthesis pathways on their own do not lead to elevated U-DNA level (Luo, Walla, & Wyatt, 2008; Róna et al, 2016; Yan et al, 2016). Following U-DNA immunoprecipitation, successful enrichment of U-DNA could be confirmed by dot blot assay in the case of drug-treated cells (5FdUR_UGI or RTX_UGI, Figure 1B).…”
Section: Resultsmentioning
confidence: 99%
“…Scale bar represents 40 μm. Note that the nuclei of the treated cells (5FdUR_UGI) are enlarged as compared to the non-treated ones (NT_UGI) presumably due to cell cycle arrest (Huehls et al, 2016; Yan et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Inhibitors of Pol β have also been developed but demonstrated only mild preclinical efficacy, and new compounds suffer from the fear of toxicity due to overlapping specificity with additional DNA polymerases [29]. Finally, recently our lab and others demonstrated that inhibition of uracil DNA glycosylase (UDG) sensitized cancer cells to thymidylate synthase (TS) inhibitors including floxuridine and pemetrexed in the preclinical setting, providing rationale for further development of UDG inhibitors [30,31]. …”
Section: Introductionmentioning
confidence: 99%